Integration of Dayak Culture in Women's Leadership to Improve the Quality of Digital Education in Elementary Schools: Integrasi Budaya Dayak Dalam Kepemimpinan Perempuan Untuk Peningkatkan Mutu Pendidikan Digital Di Sekolah Dasar - Handayani, Lisa; Gede, Widyatmike; Azainil (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
This research focuses on the role of women's leadership in integrating Dayak culture to improve the quality of digital-based education in elementary schools in Samarinda, East Kalimantan. With a qualitative approach through observation, in-depth interviews, and document analysis, this study identifies how women's leadership can facilitate the adoption of digital technologies while maintaining local cultural values. The results of the study show that Dayak women who lead in schools have a strategic role in designing educational policies that combine elements of technology with traditional culture, creating a more inclusive and relevant learning environment for students. Despite challenges, such as limited digital infrastructure and community resistance, women's leadership has proven effective in improving students' understanding of local cultures while preparing them for the digital world. Women's leadership plays an important role in strengthening the integration of local culture in digital education, increasing the competitiveness of education in East Kalimantan. It is recommended that there be technology training for women educators and increased access to digital infrastructure in elementary schools to support the success of this integration.